Measuring the Boundaries of Criminal Liability for Obscene Acts in Medical Treatments (Case Study of Decision Number 114/Pid.Sus/2021/PN.Idi) - Y.A. Triana ohoiwutun; Sapti Prihatmini; Windy Puri Astuti; Aleya Zeneizha (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Objectives of the study: This study examined the boundaries of criminal liability for the obscene act of doctors in providing medical treatments to patients beyond their authority. In addition, this study further investigated the panel of judge ratio decidendi towards the case. Methodology: This study employed a doctrinal method with a statutory approach, a conceptual approach, and a qualitative analysis. Results: The defendant's actions in Decision Number 114/Pid.Sus/2021/PN.Idi is categorized as malpractice or obscene acts, in which determining parameters are related to acts of violation of medical ethics, medical discipline and/or violations of criminal law. The assessment of the boundaries of criminal liability of doctors in the process of proving a case in court requires information from examination sessions by the MKEK and/or MKDI institutions. The role of MKEK and/or MKDI is urgent; however, their authorities are dissimilar, and the results of their examinations do not bind the criminal court decision. Applications of this study: This study evaluated the liability of doctors in both criminal and ethical liability. In addition, this study serves as an evaluation tool for judges' logical approach. Novelty/ Originality of this study: This study examined the criminal and ethical liability of doctors in a case study. Keywords: Malpractice, Standard Operating Procedure, Competency Standard ABSTRAK Tujuan: Penelitian ini mengkaji batas-batas pertanggungjawaban pidana atas perbuatan cabul dokter dalam memberikan perawatan medis kepada pasien di luar kewenangannya. Selain itu, penelitian ini menyelidiki lebih lanjut tentang pertimbangan majelis hakim (rasio decidendi) terhadap kasus tersebut. Metodologi: Penelitian ini menggunakan metode doktrinal dengan pendekatan statute (perundang-undangan), pendekatan konseptual, dan analisis kualitatif. Temuan: Tindakan tergugat dalam Putusan Nomor 114/Pid.Sus/2021/PN.Idi dikategorikan sebagai malpraktik atau perbuatan cabul, dimana parameternya mengacu pada tindak pelanggaran etika kedokteran, disiplin kedokteran, dan/atau pelanggaran hukum pidana. Penilaian batas-batas pertanggungjawaban pidana dokter dalam proses pembuktian suatu perkara di pengadilan memerlukan keterangan dari sesi pemeriksaan yang dilakukan oleh lembaga MKEK dan/atau MKDI. Peran MKEK dan/atau MKDI sangat penting, namun kewenangan dua lembaga tersebut berbeda, dan hasil pemeriksaan dua lembaga ini tidak mengikat pada putusan MK. Kegunaan: Penelitian ini mengevaluasi tanggung jawab dokter dalam pertanggungjawaban pidana dan etika. Selain itu, penelitian ini berfungsi sebagai alat evaluasi untuk pendekatan logis para hakim. Kebaruan/Orisinalitas: Penelitian ini mengkaji tanggung jawab pidana dan etika para dokter dalam sebuah studi kasus. Kata kunci: Malpraktik, Standar Operasional Prosedur, Standar Kompetensi